2019
DOI: 10.1111/aogs.13703
|View full text |Cite
|
Sign up to set email alerts
|

Live birth and miscarriage rate following intracytoplasmic morphologically selected sperm injection vs intracytoplasmic sperm injection: An updated systematic review and meta‐analysis

Abstract: IntroductionIntracytoplasmic morphologically selected sperm injection (IMSI) is one of the sperm selection techniques used for assisted reproduction which has been applied for a variety of indications including previously failed fertilization with intracytoplasmic sperm injection (ICSI). A Cochrane review1 found no difference in outcomes between either modality of sperm selection. Since the Cochrane review was published there have been a further two randomized controlled trials comparing IMSI and ICSI. This sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Recently, high-powered differential interference contrast optics provided a novel means to improve the selection of morphologically superior spermatozoa under ultra-high magnification of Â10,160: intracytoplasmic morphologically selected sperm injection (IMSI). Notwithstanding some reports of increased success, a recent metaanalysis of randomized studies comparing IMSI and ICSI has not shown a difference in live birth or miscarriage rate (143). A bibliographic analysis revealed consensus for the following findings: 1) head sperm vacuoles appear frequently, often multiple and preferentially anterior; 2) sperm vacuoles and sperm chromatin immaturity are related; and 3) teratozoospermia could be a preferred indication of IMSI (144).…”
Section: Intracytoplasmic Sperm Injectionmentioning
confidence: 99%
“…Recently, high-powered differential interference contrast optics provided a novel means to improve the selection of morphologically superior spermatozoa under ultra-high magnification of Â10,160: intracytoplasmic morphologically selected sperm injection (IMSI). Notwithstanding some reports of increased success, a recent metaanalysis of randomized studies comparing IMSI and ICSI has not shown a difference in live birth or miscarriage rate (143). A bibliographic analysis revealed consensus for the following findings: 1) head sperm vacuoles appear frequently, often multiple and preferentially anterior; 2) sperm vacuoles and sperm chromatin immaturity are related; and 3) teratozoospermia could be a preferred indication of IMSI (144).…”
Section: Intracytoplasmic Sperm Injectionmentioning
confidence: 99%
“…IMSI is one of the sperm selection techniques used in assisted reproduction, with application indicated for cases of male factor infertility and failed ICSI. IMSI includes strict sperm morphological investigation performed under magnifications of 6600-10000x and reportedly improves clinical and perinatal outcomes (Duran-Retamal et al, 2020). The use of MSOME for sperm selection before ICSI has been discussed by several authors regarding the improvement of clinical results including clinical pregnancy and live birth rates; however, trials rarely provide information on perinatal information (Antinori et al, 2008;Marci et al, 2013;Gatimel et al, 2016;He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, a meta‐analysis conducted by Teixeira and colleagues indicated that nine randomised controlled trials (RCTs) exhibited no supporting evidence for the effectiveness of IMSI routine clinical use (Teixeira et al., 2013). Such findings are further justified by the up‐to‐date Cochran review (Teixeira et al., 2020), and the latest meta‐analysis study involving six RCTs (Duran‐Retamal et al., 2020). The potential benefits of IMSI practice remain inconclusive.…”
Section: Introductionmentioning
confidence: 95%